Inactivity-induced NR4A3 downregulation in human skeletal muscle affects glucose metabolism and translation: Insights from in vitro analysis - Jonathon A.B. Smith; Brendan M. Gabriel; Aidan J. Brady; Ahmed M. Abdelmoez; Mladen Savikj; Shane C. Wright; Stefania Koutsilieri; Romain Barrès; Volker M. Lauschke; Anna Krook; Juleen R. Zierath; Nicolas J. Pillon (Molecular Metabolism, 2025)
Objective: Physical activity promotes health, whereas inactivity is associated with metabolic impairment. The transcription factor nuclear receptor subfamily 4 group A member 3 (NR4A3) is a pleiotropic regulator of skeletal muscle exercise adaptation and metabolism. However, the consequence of lower NR4A3 expression remains largely unexplored. We investigated the impact of NR4A3 downregulation on human skeletal muscle metabolism. Methods: Published transcriptomic datasets from human bed rest and limb immobilisation studies were curated to meta-analyse the effect of physical inactivity on skeletal muscle NR4A3 levels. In primary human skeletal myotubes, siRNA and lentivirus were used to silence and overexpress NR4A3, respectively. Basal and stimulated (insulin ± leucine) signal transduction was determined by immunoblot analysis. Effects on glucose, fatty acid, and protein metabolism were measured using radiolabelled substrate assays. Lactate production was assessed in culture supernatant by colourimetry. Cell morphology was analysed by immunocytochemistry and gene expression was quantified by RT-qPCR. Results: Physical inactivity decreased skeletal muscle NR4A3 (−27%), concomitant with pathways related to mitochondrial function, cytoskeleton organization, chromatin regulation, protein synthesis and degradation. Silencing of NR4A3 reduced glucose oxidation (−18%) and increased lactate production (+23%) in vitro. This coincided with greater signalling downstream of AMPK and elevated rates of basal (+26%) and FCCP-stimulated (+55%) fatty acid oxidation. NR4A3 downregulation lowered protein synthesis (−25%), and impaired mTORC1 signalling and ribosomal transcription. Alternatively, overexpression of the canonical NR4A3 protein isoform (+290%) augmented translation and total cellular protein content, which protected myotubes against dexamethasone-induced atrophy. Moreover, partial restoration of NR4A3 levels rescued glucose oxidation in NR4A3-silenced muscle cells and restored phosphorylation of mTORC1 substrates. NR4A3 depletion reduced myotube area (−48%) and further altered protein and gene expression of key contractile elements in skeletal muscle. Conclusions: Our study connects reduced NR4A3 expression with physical inactivity and indicates that NR4A3 downregulation in human skeletal muscle has adverse effects on glucose metabolism and protein synthesis. Thus, decrements in NR4A3 abundance could be causal in the deleterious health consequences resulting from sedentary lifestyles and targeting NR4A3 may offer new avenues for combating conditions such as disuse muscle atrophy.